Tax Avoidance in Consumer Non-Cyclicals Companies in Indonesia : Board Gender Diversity, Executive Characters, Executive Compensation, and Family Ownership - Maharani, Dhela Gulfianti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study empirically examines the effect of board gender diversity, executive character, executive compensation, and family ownership on tax avoidance in consumer non-cyclical companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. This quantitative research utilizes secondary data from 136 sample companies, selected through a purposive sampling method and accessed from www.idx.co.id. The results of the multiple regression analysis performed in IBM SPSS 26 indicate that executive character and family ownership have a positive and significant effect on tax avoidance, while executive compensation has a negative and significant effect. Meanwhile, board gender diversity has no effect on tax avoidance.